2015
DOI: 10.1007/s11356-015-4974-9
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin accumulation in bighead carp (Aristichthys nobilis) during a Microcystis-dominated bloom and risk assessment of the dietary intake in a fish pond in China

Abstract: Microcystins (MCs) produced by cyanobacteria can accumulate in freshwater fish tissues and pose potential risk to human health. In this study, variations in MC content were examined in water samples and fish tissues during a Microcystis aeruginosa-dominated bloom in a fish pond in China, from June 2009 to August 2009. A total of ten microcystin variants were detected in water samples in the fish pond, including MCLR, MCRR, MCYR, MCLF, MCLY, MCLA, and MCLW, and other three undefined MC variants. MCLR was the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Additionally, fish that feed on potentially toxigenic cyanobacteria, have a direct path of cyanotoxin exposure that is presumably insignificant or nonexistent for carnivorous fish. Among the tissues, the concentrations of cyanotoxins, specifically microcystins, are often reported to be higher in liver, kidney, and intestine relative to concentrations in the muscle (Mekebri et al, 2009;Amrani et al, 2014;Ni et al, 2017). We expected the assembled data on fish tissues to parallel these observations.…”
Section: Introductionmentioning
confidence: 89%
“…Additionally, fish that feed on potentially toxigenic cyanobacteria, have a direct path of cyanotoxin exposure that is presumably insignificant or nonexistent for carnivorous fish. Among the tissues, the concentrations of cyanotoxins, specifically microcystins, are often reported to be higher in liver, kidney, and intestine relative to concentrations in the muscle (Mekebri et al, 2009;Amrani et al, 2014;Ni et al, 2017). We expected the assembled data on fish tissues to parallel these observations.…”
Section: Introductionmentioning
confidence: 89%
“…The main route of human exposure to MC-LR is the ingestion of contaminated water and/or food. Fish food products are considered the main vectors of cyanotoxins (Hardy et al, 2015, Ni et al, 2015; nevertheless, toxin transfer may also occur with consumption of horticultural products. Indeed, several studies have already reported the accumulation of MCs in agricultural food products (Corbel et al, 2014a, Romero-Oliva et al, 2014 and suggest the use of surface water contaminated with MC-LR as the main cause of contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Such discrepancies have also been found in other studies. For instance, Ni et al [65] found seven MC variants, including MC-RR in the seston, but only two variants (MC-LR and MC-LY) in the liver of Bighead carp (species); Xie et al [66] raised silver carp in tanks with MC-RR and MC-LR containing Microcystis, but found mostly only MC-RR in carp liver. Moreover, differences in relative abundances of MC-variants in different tissues has been observed, yet a clear physiological mechanism explaining the obvious differences in carp liver and surrounding seston is still lacking [66].…”
Section: Cyanotoxins In Biota At Prespa Areamentioning
confidence: 99%
“…Although carp liver is not consumed by humans, it is highly likely that also the muscle tissue of these fish contained MCs. Several studies that examined different carp tissues on MCs found either comparable concentrations in these tissues as in the liver [57] or between to 25 times lower concentrations [58,60,63,65,67]. Besides accumulation of MCs fish may also accumulate off-flavors produced by cyanobacteria that may lead to a lower quality for consumption and hence may have economic consequences as a result of reduced fish consumption [68].…”
Section: Cyanotoxins In Biota At Prespa Areamentioning
confidence: 99%